2017
DOI: 10.18520/cs/v113/i02/322-329
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity of White Grubs (Coleoptera:Scarabaeidae) in the Sub-Himalayan and Northern Plains of India

Abstract: White grubs belonging to subfamilies Melolonthinae and Rutelinae of Scarabaeidae (Coleoptera) are ubiquitous pests. Studies during 2013 and 2014 document the species diversity of white grubs in the subHimalayan and northern plains of India. Surveys conducted in four states, viz. Himachal Pradesh, Uttarakhand, Uttar Pradesh and Rajasthan revealed high species diversity representing 65 species under 16 genera. The species richness, evenness and composition varied among the states. Higher species diversity was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The present observations are in conformity with those of Aparna et al (2018) on Melolonthinae being the dominant taxon. Similar results were known from other regions (Dadmal and Khadakkar, 2014;Pathania et al, 2015;Sreedevi et al, 2017). Observations revealed that five species could account to nearly 79% of the total faunistic diversity in the Dakshina Kannada.…”
Section: Resultssupporting
confidence: 87%
“…The present observations are in conformity with those of Aparna et al (2018) on Melolonthinae being the dominant taxon. Similar results were known from other regions (Dadmal and Khadakkar, 2014;Pathania et al, 2015;Sreedevi et al, 2017). Observations revealed that five species could account to nearly 79% of the total faunistic diversity in the Dakshina Kannada.…”
Section: Resultssupporting
confidence: 87%
“…In another subfamily Rutelinae are Anomala bengalensis, and A. dimidiata are polyphagus white grubs and dangerous pests of agricultural and horticultural crops. Present finding are supported by Sreedevi et al (2017) . In Rajasthan, H. consanguinea and M. insanabilis, are the predominant species and serious pests of groundnut, bajra and jowar.…”
Section: Resultssupporting
confidence: 86%
“…Species distribution is important strategy for species specific management options. Previous reports provide list of scarab fauna in north India (Sreedevi et al, 2017). Geographical variations united with cropping pa ern differences contribute to composition of species complex of an area.…”
Section: Resultsmentioning
confidence: 99%
“…A species diversity study is vital for planning the pest management practices. Geographical variations with cropping pattern differences contribute to the composition of species complex of a region (Sreedevi et al 2017). Hence, a diversity study of dung beetles would be helpful to the concerned authority in pest management options.…”
Section: Journal Of Threatened Taxamentioning
confidence: 99%